Upaya Meningkatkan Hasil Belajar Dan Kemampuan Gerak Dasar Permainan Rounders Melalui Strategi Pembelajaran Berpasangan Siswa Kelas V SD - Bunga Bunga (Universtas Negeri Makassar, 2022)
The purpose of this study is to improve the basic movement skills of the rounders game through paired strategies in class V SD Negeri 206 Apala. From the results of classroom action research that was carried out that the application of paired learning strategies had a positive impact on increasing the ability to throw and catch the ball of fifth grade students at SD Negeri 206 Apala, this can be proven. The increase in student learning outcomes is marked by an increase in student learning outcomes and mastery in each cycle, namely 4 students or 17.39%, in the first cycle there was an increase, namely there were 10 students or 43.48%, and in the second cycle there were 20 students or 86.96%, this result was in accordance with the specified indicator, namely the score with KKM 70 above 85 % with the acquisition of the average value in the initial conditions of 56.52, increased to 61.74 in the first cycle and 73.04 in the second cycle. From the results as described above, it can be concluded that the application of paired learning strategies is proven to be able to improve the basic movement skills of throwing and catching the ball in the rounders game..